2021
DOI: 10.1016/j.transci.2021.103195
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling whole blood processing through automation and pathogen reduction technology at the Luxembourg Red Cross

Abstract: In 2014-2015, the Luxembourg Red Cross (LRC) implemented a fully automated system (FAS) able to process 4 whole blood units simultaneously, and a pathogen reduction technology (PRT) based on riboflavin and ultraviolet light to improve safety of platelet concentrates (PCs). In this observational study, the impact of both technologies to enable this centralised blood transfusion centre to provide safe and timely blood components supply for the whole country was analysed. Standard quality control parameters for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
2
12
0
2
Order By: Relevance
“…A list of excluded studies can be found in Supporting information S1. Overall, 17 studies were included in the analysis, with publication years ranging from 2004 to 2021 [5–7, 9, 15–27]. Manual search resulted in a further six publications for inclusion [8, 11, 28–31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A list of excluded studies can be found in Supporting information S1. Overall, 17 studies were included in the analysis, with publication years ranging from 2004 to 2021 [5–7, 9, 15–27]. Manual search resulted in a further six publications for inclusion [8, 11, 28–31].…”
Section: Resultsmentioning
confidence: 99%
“…The comparison accounted for the time for processing, filtering RBCs and platelets by gravity and pooling interim platelet units (IPUs) with SSP+ platelet additive solution (PAS) [18]. Moreover, the increased productivity and efficiency due to a reduction in time from 196 to 137 min from semi‐automated to fully automated processing of 12 whole blood donations did not impact quality [23]. It is important to highlight that the IPU obtained with the Reveos system is a highly concentrated platelet product in approximately 30 ml plasma, which can be pooled with plasma or PAS to create a platelet concentrate without requiring any additional centrifugation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogen reduction of blood products has been routinely practiced for over 15 years in many centers across the world and recently in the United States [19][20][21][22]. These methods for cellular blood components rival the use of technologies to protect the fractionated plasma component products derived from donated and renumerated blood donations in their ability to achieve inactivation of a wide range of pathogens under routine process conditions.…”
Section: Introductionmentioning
confidence: 99%